Al-Mal (Hak Milik) dalam Perspektif Fuqaha - Ahdiyat Agus Susila (Fakultas Ekonomi dan Bisnis Islam, 2017)
Islam has a unique view of property rights, because it is collaborated from the Qur’an and Al-Hadith. In Islamic view the absolute owner of the whole universe is Allah (Q.S. Ali Imran, 3: 189) whereas man is the relative owner. Human ownership is bound by God’s rule, it is only duty to carry out God’s commands upon the processing of the universe. The realization that human ownership of economic resources will be accountable to God in the afterlife will encourage people to be careful to manage property rights. In general it can be said that Islam provides a proportional position between individual property rights, collective property rights (common) and state property rights. Although these property rights are highly protected, they are not absolute property rights. Property rights may change or be altered according to their importance and urgency of course through justified means. Intellectual Property Rights or copyright does not exist, either the Qur’an or the transfusely transparent hadith. Thus, the problem is the problem of ijtihadiyah with the approach of maslahah theory. What is not a matter of ijtihad in Islam is what is clearly known about aqeedah and worship. In this case muamalah (human relations) issues in wide range wide open for ijtihad, for the benefit of human beings. Here also revealed the dynamism of Islamic law in staring and responding to the progress of the times